2017
DOI: 10.1007/s00105-016-3918-8
|View full text |Cite
|
Sign up to set email alerts
|

Akne und Rosazea in der Schwangerschaft

Abstract: Acne and rosacea are common chronic inflammatory skin diseases. During pregnancy these skin disorders may become aggravated, in rare cases occurring for the first time. There are no data available for rosacea and little data for acne concerning the course of these skin disorders during pregnancy. Up to 42% of the pregnant women suffer from acne. In 90% of these women the disease existed before pregnancy. In 1/3, however, acne relapsed during pregnancy after a prior disease-free period. In 60% acne deteriorated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In addition, the prevalence of acne during pregnancy was 45.9%, similar to what was seen in the literature, which revealed that 42% of pregnant women were affected [37]. However, in our study, less than half of the patients had previously had acne, in contrast to 90% in the study by Bechstein, et al [37].…”
Section: Acnesupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the prevalence of acne during pregnancy was 45.9%, similar to what was seen in the literature, which revealed that 42% of pregnant women were affected [37]. However, in our study, less than half of the patients had previously had acne, in contrast to 90% in the study by Bechstein, et al [37].…”
Section: Acnesupporting
confidence: 89%
“…In addition, the prevalence of acne during pregnancy was 45.9%, similar to what was seen in the literature, which revealed that 42% of pregnant women were affected [37]. However, in our study, less than half of the patients had previously had acne, in contrast to 90% in the study by Bechstein, et al [37]. In this context, during the course of pregnancy, hormonal changes occur that generate not only the aggravation, but also the inhibition of acne [38].…”
Section: Acnesupporting
confidence: 88%
“…A comprehensive review of acne treatment during pregnancy can be found elsewhere [ 37 ] . Retinoids (topical and systemic) as well as tetracyclines are contraindicated.…”
Section: Continuedmentioning
confidence: 99%
“…Many women see an exacerbation of their rosacea in pregnancy, with hormonal changes causing increased cutaneous vascularity, seborrhoea and dermal oedema 65. It can also occur for the first time in pregnancy 66…”
Section: Managing Skin Diseases During Pregnancymentioning
confidence: 99%